2010
DOI: 10.1159/000309756
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Anti-Inflammatory Annexin A1 Protein and Tacrolimus Immunosuppressant in the Renal Function of Rats

Abstract: Background: Tacrolimus (FK) is currently widely used in transplant immunosuppression and the treatment of autoimmune diseases. However, FK induces nephrotoxicity which is characterized by functional and structural renal injury. The ubiquitous protein annexin A1 (ANXA1) has potent anti-inflammatory effects and protects against ischemia/reperfusion injury. We investigated the effects of exogenous ANXA1 treatment in an experimental model of acute FK nephrotoxicity. Methods: Munich-Wistar rats received a low-salt … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Similarly, we have shown that salt-depleted tacrolimus treatment augments renal ANXA1 expression [25]. ANXA1 expression has previously been shown to increase in response to glucocorticoids [38], inflammation [28], heat or chemical cellular damage [39] and proinflammatory cytokines [40].…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Similarly, we have shown that salt-depleted tacrolimus treatment augments renal ANXA1 expression [25]. ANXA1 expression has previously been shown to increase in response to glucocorticoids [38], inflammation [28], heat or chemical cellular damage [39] and proinflammatory cytokines [40].…”
Section: Discussionsupporting
confidence: 59%
“…After anesthesia, rats underwent renal hemodynamic studies as previously described [25]. RBF measurements were taken (T 106, Transonic Systems Inc., NY, USA) during 40 min.…”
Section: Renal Blood Flowmentioning
confidence: 99%
See 2 more Smart Citations
“…Ubd, which encodes a protein called Fat10, has been shown to be a pro-apoptotic and pro-inflammatory protein in HIVAN [16]. Interestingly, Anxa1 has been reported to display anti-inflammatory effects [17]. Spon1 is a novel candidate gene for hypertension [18].…”
Section: Resultsmentioning
confidence: 99%